Efficacy and safety of intracavitary electrocardiography-guided peripherally inserted central catheters in pediatric patients: a systematic review and meta-analysis - Li Zhang; Min Wang; Mingjia Zhao; Siyi Pu; Jiao Zhao; Ge Zhu; Qin Zhang; Dan Li (PeerJ, 2024)
Objective To assess the efficacy and safety of intracavitary electrocardiography (IC-ECG)-guided peripherally inserted central catheter (PICC) placements in pediatric patients, emphasizing improvements over traditional placement methods. Methods A literature search was conducted in April 2024 across PubMed, Cochrane Library, and EMBASE. Studies focusing on pediatric patients and reporting the efficacy and safety of IC-ECG-guided PICC placement via the upper extremity were included. This study was registered with the PROSPERO database (CRD42024549037) in accordance with PRISMA guidelines. Results Eleven studies were included, comprising five randomized controlled trials (RCTs) and six quasi-experimental studies. The pooled analysis showed that IC-ECG had an applicability and feasibility of 97% and 98%, respectively. The first puncture success rate was 91%, and the overall success rate was 98%. Sensitivity and specificity were 97% and 80%, respectively. IC-ECG significantly reduced overall complications compared to traditional methods (RR: 0.31, 95% CI [0.20–0.46], p < 0.00001), particularly in phlebitis (RR: 0.25, 95% CI [0.11–0.57], p = 0.001) and arrhythmias (RR: 0.09, 95% CI [0.01–0.70], p = 0.021). Similar results were observed in neonates. Only one case of catheter-related bloodstream infection (CRBSI) was reported, and no arrhythmia events were noted. Conclusion IC-ECG-guided PICC placement is a highly effective and safe method for pediatric patients, including neonates, offering significant advantages over traditional techniques. Further high-quality studies are needed to standardize procedural techniques and explore cost-effectiveness.